Polymer PCF Bragg grating sensors based on poly(methyl methacrylate) and TOPAS cyclic olefin copolymer - Kalli, Kyriacos; Webb, David J.; Johnson, Ian P.; Yuan, Wu; Stefani, Alessio; Nielsen, Kristian Fog Og; Rasmussenc, Henrik K.; Bang, Ole (My University, 2011)
Fibre Bragg grating (FBG) sensors have been fabricated in polymer photonic crystal fibre (PCF). Results are presented using two different types of polymer optical fibre (POF); first multimode PCF with a core diameter of 50μm based on poly(methyl methacrylate) (PMMA) and second, endlessly single mode PCF with a core diameter of 6μm based on TOPAS cyclic olefin copolymer. Bragg grating inscription was achieved using a 30mW continuous wave 325nm helium cadmium laser. Both TOPAS and PMMA fibre have a large attenuation of around 1dB/cm in the 1550nm spectral region, limiting fibre lengths to no longer than 10cm. However, both have improved attenuation of under 10dB/m in the 800nm spectral region, thus allowing for fibre lengths to be much longer. The focus of current research is to utilise the increased fibre length, widening the range of sensor applications. The Bragg wavelength shift of a grating fabricated in PMMA fibre at 827nm has been monitored whilst the POF is thermally annealed at 80 °C for 7 hours. The large length of POF enables real time monitoring of the grating, which demonstrates a permanent negative Bragg wavelength shift of 24nm during the 7 hours. This creates the possibility to manufacture multiplexed Bragg sensors in POF using a single phase mask in the UV inscription manufacturing. TOPAS holds certain advantages over PMMA including a much lower affinity for water, this should allow for the elimination of cross-sensitivity to humidity when monitoring temperature changes or axial strain, which is a significant concern when using PMMA fibre.
Keywords: Bragg gratings; Cadmium; Copolymers; Crystal whiskers; Esters; Fibers